2002
DOI: 10.1111/j.1365-2621.2002.tb08742.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Listeria monocytogenes, Salmonella spp., and Escherichia coli O157:H7 During Processing of Country‐cured Hams

Abstract: The country-cured ham process, including curing, equalization, cold-smoked or nonsmoked, and aging up to 6 mo, was validated and showed its effectiveness in achieving a 6-log reduction of Listeria monocytogenes, Salmonella spp., and Escherichia coli O157:H7. The viable counts of L. monocytogenes populations decreased to below detection levels after 206 d, Salmonella populations required 122 d, and E. coli O157:H7 required 66 d. However, L. monocytogenes-inoculated hams were positive and Salmonella spp-inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…So far, very few studies focused on the drycured ham production process (Barbuti, Ghisi, & Campanini, 1989;Giovannini et al, 2007). Also, previous Authors have documented the occurrence of L. monocytogenes in dry-cured ham following experimental inoculation (Grisenti et al, 2004;Portocarrero, Newman, & Mikel, 2002;Reynolds, Harrison, Rose-Morrow, & Lyon, 2001;Wool, Langlois, & Moody, 1998). To date, information on L. monocytogenes contamination routes in Parma ham during processing is still lacking.…”
Section: Introductionmentioning
confidence: 92%
“…So far, very few studies focused on the drycured ham production process (Barbuti, Ghisi, & Campanini, 1989;Giovannini et al, 2007). Also, previous Authors have documented the occurrence of L. monocytogenes in dry-cured ham following experimental inoculation (Grisenti et al, 2004;Portocarrero, Newman, & Mikel, 2002;Reynolds, Harrison, Rose-Morrow, & Lyon, 2001;Wool, Langlois, & Moody, 1998). To date, information on L. monocytogenes contamination routes in Parma ham during processing is still lacking.…”
Section: Introductionmentioning
confidence: 92%
“…These findings demonstrate that the Westphalian ham dry-curing procedures used did not irreversibly eliminate E. coli O157 : H7 cells. Previous research demonstrated that 112 and ≤206 days, respectively, 16,14 were required to eliminate large numbers of E. coli O157 : H7 from dry-cured ham surfaces after enrichment. It is likely that an extension of the drying phase of the process used in the present study could be used in conjunction with a slightly higher storage temperature to irreversibly eliminate E. coli O157 : H7 cells.…”
Section: Westphalian Ham Microbiological Changesmentioning
confidence: 99%
“…Since pork meat may become cross-contaminated with enteric organisms during processing, 12,13 some types of country-cured ham processing have been examined and found capable of reducing E. coli O157 : H7 by >7 log 10 CFU g −1 after 90 and 66 days, 14,15 respectively. Alternatively, a dry-cured Westphalian ham process in which raw hams were needle-tenderized to facilitate cure penetration was found to reduce surface E. coli O157 : H7 by >7 log 10 CFU g −1 after 112 days but internalized E. coli O157 : H7 cells remained viable.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, dry cured ham manufacture involving extended drying periods (>234d) completely eliminated the pathogen from the product, and analysis revealed that no viable cells were found after enrichment (Portocarrero et al 2002). Risk associated with potential survival of E. coli O157:H7 during dry cured ham manufacture may be reduced by extension of drying intervals, however this increases processing cost.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogen was reduced by 5 log cfu·g -1 at the end of the ripening period (80d) by the dry cure process. In another study by Portocarrero et al (2002), it took 66d ripening to decrease E. coli O157:H7 to below the detection limit in country-cured hams initially inoculated with 7-8 log cfu·g -1 E. coli O157:H7. The hams made by Portocarrero et al (2002) were held for a longer ripening period (234d) than the other studies, which resulted in the complete elimination of E.…”
Section: Regulations In Place Involving Fermented Meat Products and Ementioning
confidence: 99%